Psychosocial and environmental risk factors of obesity and hypertension in children and adolescents: a literature overview - Wójcik, Małgorzata; Alvarez-Pitti, Julio; Kozioł-Kozakowska, Agnieszka; Brzeziński, Michał; Gabbianelli, Rosita; Herceg-Čavrak, Vesna; Wühl, Elke; Lucas, Ignacio; Radovanović, Dragan; Melk, Anette; González Lopez-Valcarcel, Beatriz; Fernández-Aranda, Fernando; et al. (Frontiers in Cardiovascular Medicine, 2023)
Childhood obesity has become a worldwide epidemic in the 21st century. Its treatment is challenging and often ineffective, among others due to complex, often not obvious causes. Awareness of the existence and meaning of psychosocial and environmental risk factors seems to be an essential element in the prevention and treatment of obesity and its complications, especially arterial hypertension. In this review, we will discuss the role of that risk factors linking obesity and increased cardiovascular disorders including the role of nutritional factors (including the role of unhealthy diet, inadequate hydration), unhealthy behaviors (e.g. smoking, alcohol and drugs, sedentary behavior, low physical activity, disrupted circadian rhythms, sleep disorders, screen exposure), unfavorable social factors (such as dysfunctional family, bullying, chronic stress, mood disorders, depression, urbanization, noise, and environmental pollution), and finally differences in cardiovascular risk in girls and boys.
Gesehen am 12.04.2024